GLORIA Chemistry Mode temperature and trace gas retrievals from the POLSTRACC/GW-LCYCLEII/GWEX/SALSA campaigns 2015/2016 - Johansson, Sören; Woiwode, Wolfgang; Höpfner, Michael (2018)
The Gimballed Limb Observer for Radiance Imaging of the Atmosphere (GLORIA) was operated on board the German High Altitude and Long Range Research Aircraft (HALO) during the PGS (POLSTRACC/GW-LCYCLE/SALSA) aircraft campaigns in the Arctic winter 2015/2016. Research flights were conducted from 17 December 2015 until 18 March 2016 within 25–87°N, 80°W–30°E. From the GLORIA infrared limb-emission measurements, two-dimensional cross sections of temperature, HNO3, O3, ClONO2, H2O and CFC-12 are retrieved. During 15 scientific flights of the PGS campaigns the GLORIA instrument measured more than 15000 atmospheric profiles at high spectral resolution. Dependent on flight altitude and tropospheric cloud cover, the profiles retrieved from the measurements typically range between 5 and 14km, and vertical resolutions between 400 and 1000m are achieved. The estimated total (random and systematic) 1σ errors are in the range of 1 to 2K for temperature and 10% to 20% relative error for the discussed trace gases.